Eleições, mídia e memória: uma análise do jornal Folha de S. Paulo - Esteves, Gabriel Papa Ribeiro [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
This research aims to understand the relationship between media and politics in both pre-election and election periods during the Brazilian presidential elections in 2010 in order to capture how the memorial representation of the past is in the Brazilian society when it comes to the military regime (1964-1985), a period that left deep scars in this society. We chose to analyze the coverage done by the newspaper Folha de São Paulo, for it is one of the major media to cover the national elections. We aim to analyze the content in every piece of news in the newspaper from 03/01/2010 to 11/06/2010 and how the newspaper portraits the candidates, building their images from their respective pasts as military regime opponents, reflecting how the representation by Folha about the memory of the Brazilian civil-military dictatorship period is done during the coverage of the 2010 elections

Esta pesquisa busca compreender a relação entre mídia e política nos períodos pré-eleitoral e eleitoral das eleições presidenciais de 2010, para captar como se dá a representação memorial do passado na sociedade brasileira, acerca do regime militar (1964-1985), período que deixou marcas profundas nessa sociedade. Escolhemos analisar a cobertura feita pelo jornal Folha de São Paulo, pelo fato de ser um dos principais meios de comunicação a cobrir as eleições nacionais. Visamos analisar o conteúdo, em todos os fragmentos presentes no jornal, de 01/03/2010 a 06/11/2010. E como o jornal retrata os candidatos, construindo suas imagens a partir de seus respectivos passados opositores ao regime, refletindo como se dá a representação feita pela Folha acerca da memória do período da ditadura civil-militar brasileira ao cobrir as eleições de 2010
Keywords: Folha de S. Paulo (Jornal); Eleições; Comunicação de massa - Aspectos políticos; Mass media Political aspects; Brasil - História - 1964-1985